Inovasi Teknlogi dalam Kebersihan Pribadi dan Lingkungan Sekitar - Judiono Judiono; Rayhan Surya Permana; Cilda Thesisa Ilmawan Dzinnur; Yayu Sriwahyuni Hamzah; Yeni Vitrianingsih (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2026)
Waste management innovation is needed to address these waste issues. Halvorsen's theories on innovation focus on the procurement of technology and the development of technological innovations to improve personal and environmental hygiene using the Participatory Action Research (PAR) method. The PAR method was chosen because it involves active community participation in designing, implementing, and evaluating technological solutions relevant to local needs. The research focuses on the application of smart devices, digital applications, and automated sensor systems to support clean and healthy living behaviors. The results show that community involvement in the innovation process strengthens a sense of ownership, increases the effectiveness of technology implementation, and encourages the sustainability of hygiene practices. Thus, participatory technological innovation not only improves the quality of personal hygiene but also creates a healthier, safer, and more sustainable environment.